Intraoperative measurement of human spactic gracilis muscle isometric forces as a function of knee angle - Aytürk, Fatma Oya. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 2011., 2011)
Spasticity is a neuromuscular disease which is associated with increased muscle tone, stiffness and impaired motor control and consequently functional limitations. Improved understanding of spasticity requires the collection of substantial directly measured length-force characteristic of spastic muscles. Studies including direct measurement of human muscle force are very rare due to limited access to the muscle. With the method developed in this study, isometric length (knee angle) -force characteristics of human spastic Gracilis muscle are measured intraoperatively for the first time in literature. Experimental data is collected during the surgical operations performed by Prof. Dr. Yener Temelli and his group in İstanbul University School of Medicine. In 7 subjects (average age: 8 4.6), isometric muscle forces are measured by buckle force transducers at five different knee angles (of 120°, 90°, 60°, 30° and 0°). Mean peak Gracilis muscle force and mean optimal knee angles are measured to be 41.19 + 41.07 N and 30 + 31.6 respectively. knee-angle force characterisitics of 7 subjects showed inter-subject variability and peak Gracilis muscle forces were not correlated with the antropometric data of subjects. Gracilis muscle exerted non-zero force in each condition indicating that functional joint range of motion is at least as wide as from full knee extension to 120° of knee flexion. A finding of major importance is that knee angle-force characteristics of spastic Gracilis muscle are found to be not representative of the pathological condition occurring at the joint and are comparable with the ones obtained from healthy subjects in a previous study of our research group. Moreover, length history of muscle was shown presently to affect muscle force in most of the subjects.|Keywords : Cerebral palsy, Gracilis muscle, Intraoperative muscle force measurement.
Keywords: Cerebral palsy.; Muscle strength.